Propuesta de un modelo de Diseño Organizacional para el Instituto Superior Tecnológico Cotopaxi, año 2020. - Zapata García, María Gabriela (2021)
Organizational design is the means that allows the execution of institutional strategies and, therefore, must be considered as a critical activity for the establishment of the referential framework, through which the institution will serve its clients and interrelate with the market. For this reason, the present investigation was based on the proposal of an Organizational Design model for the Instituto Superior Tecnológico Cotopaxi year 2020, based on the regulations and guidelines given by the organisms that govern the technical and technological higher education system for development. strategy and institutional strengthening. In the application of the scientific method, the research problem, the methodology, the results, the proposal for the organizational design and the validation process of experts and users were identified, a descriptive and field investigation was used, with the methods Inductive and deductive, the tools to gather information applied were structured interviews with the authorities and surveys of 80 teachers, with this the problem was identified based on an outdated, unclear structure, lack of knowledge of functions, in addition to repetitive processes and documents. With the analysis carried out, a proposal was elaborated updating the structural organization chart, presenting the value chain, the process map and the procedures of five substantive processes: POA, Linkage with the Community, Degree with the Curriculum Integration Project modality, Research Projects and registrations. The proposal was fully validated by users and experts above 87% (organic structure, value chain, map of processes and procedures) since they consider that it meets the institutional needs and requirements of the CES.